The mulberry tree - Deveraux, Jude. (New York : Atria Books, 2002)
When billionaire Jimmie Manville dies in a plane crash, his widow, Lillian, is shocked to learn Jimmie's fortune has been willed to his despised siblings.
Keywords: Widows -- Virginia -- Fiction; Life change events -- Fiction; Psychological fiction; Virginia -- Fiction